Ratio Between Positive Lymph Nodes and Total Excised Axillary Lymph Nodes as an Independent Prognostic Factor for Overall Survival in Patients with Nonmetastatic Lymph Node-Positive Breast Cancer - Hatoum, Hassan A. (Springer-Verlag, 2011)
BACKGROUND. The status of the axillary lymph nodes in nonmetastatic lymph node-positive breast cancer (BC) patients remains the single most important determinant of overall survival (OS). Although the absolute number of nodes involved with cancer is important for prognosis, the role of the total number of excised nodes has received less emphasis. Thus, several studies have focused on the utility of the axillary lymph node ratio (ALNR) as an independent prognostic indicator of OS. However, most studies suffered from shortcomings, such as including patients who received neoadjuvant therapy or failing to consider the use of adjuvant therapy and tumor receptor status in their analysis. METHODS. We conducted a single-center retrospective review of 669 patients with nonmetastatic lymph nodepositive BC. Data collected included patient demographics; breast cancer risk factors; tumor size, histopathological, receptor, and lymph node status; and treatment modalities used. Patients were subdivided into four groups according to ALNR value (<.25, .25–.49, .50–.74, .75–1.00). Study parameters were compared at the univariate and multivariate levels for their effect on OS. RESULTS. On univariate analysis, both the absolute number of positive lymph nodes and the ALNR were significant predictors of OS. On multivariate analysis, only the ALNR remained an independent predictor of OS, with a 2.5-fold increased risk of dying at an ALNR of ≥.25. CONCLUSIONS. Our study demonstrates that ALNR is a stronger factor in predicting OS than the absolute number of positive axillary lymph nodes.